The architecture of the former Carmelite Monastery in the Mali Dorohostai village in Volhynia - Rychkov, Petro (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
Monasteries of the Roman Catholic order of the Carmelites were well-represented in the historic cities of Volhynia (e.g. Berdychiv, Dubno, Vyshnivets, Kisilin, Lutsk, etc.). One of them was built in the Mali Dorohostai village, which currently is a part of the Mlyniv district in Rivne Oblast of Ukraine. This monastery, built in the mid-18th century, was closed in the 1830s, and then adapted by the Russian Tsar for the use of Orthodox Church. During the first World War, it was completely destroyed. The architecture of this monastery is almost forgotten in modern historiography. The recently discovered archival drawings from the first half of the 19th century give a good idea of the stylistic and structural characteristics of the no longer existing monastery.